The Impact of Mobile Handheld Technology on Hospital Physicians' Work Practices and Patient Care: A Systematic Review - Prgomet, Mirela (American Medical Informatics Association, 2009)
The substantial growth in mobile handheld technologies has heralded the opportunity to provide physicians with access to information, resources, and people at the right time and place. But is this technology delivering the benefits to workflow and patient care promised by increased mobility? The authors conducted a systematic review to examine evidence regarding the impact of mobile handheld technology on hospital physicians' work practices and patient care, focusing on quantification of the espoused virtues of mobile technologies. The authors identified thirteen studies that demonstrated the ability of personal digital assistants (PDAs) to positively impact on areas of rapid response, error prevention, and data management and accessibility. The use of PDAs demonstrates the greatest benefits in contexts where time is a critical factor and a rapid response crucial. However, the extent to which these devices improved outcomes and workflow efficiencies because of their mobility was largely absent from the literature. The paucity of evidence calls for much needed future research that asks explicit questions about the impact the mobility of devices has on work practices and outcomes.